Faktor Faktor Yang Mempengaruhi Kadar Glukosa Darah Pada Penderita Diabetes Militus (Pola Tidur, Pengetahuan, dan Kepatuhan Minum Obat) Di RSUD Kota Madiun - Nisa Diani Amalia; Nurwijayanti Nurwijayanti2; Agustin Widyowati (Jurnal Ners, 2026)
Diabetes Mellitus is a chronic disease with a very significant increase in prevalence resulting in high morbidity and mortality. In diabetes, uncontrolled blood sugar levels are the main factor that worsens the disease. Therefore, controlling blood glucose levels in patients is important. High blood sugar levels are caused by many factors, ranging from behavioral factors such as sleep patterns, level of knowledge, and medication adherence, which are also suspected to play a role in glycemic control. This study aims to analyze the effect of sleep patterns, level of knowledge, and medication adherence on blood glucose levels in patients with Diabetes Mellitus at RSUD Kota Madiun. This research is a quantitative study with a cross-sectional approach involving 130 respondents selected by simple random sampling. Data were collected through questionnaires and random blood glucose test results, and analyzed using the Chi-Square test and ordinal logistic regression. The results showed a significant effect between sleep patterns (p=0.000), level of knowledge (p=0.004), and medication adherence (p=0.000) on blood glucose levels. Multivariate analysis showed that sleep patterns were the most dominant variable (p=0.011), followed by medication adherence (p=0.034), while level of knowledge was not significant after being controlled together with other variables. The Nagelkerke R-Square value of 0.978 indicates that 97.8% of the variation in blood glucose levels can be explained by these three variables. It is concluded that sleep patterns and medication adherence have a significant effect on blood glucose levels, with sleep patterns as the most dominant factor.